Komparasi Model Pengembangan SDM Sekolah di Negara Maju dan Negara Berkembang dalam Implementasi TQM - Rofiqoh, Sri; Madhusen, Husen; Nurhuda, Muhamad Ihsan; Filwa, Filwa; Hamid, Abdul (Lentera: Jurnal Ilmiah Kependidikan, 2025)
The implementation of Total Quality Management (TQM) in education demands a transformation of Human Resources (HR) from administrative executors to autonomous agents of change. This study aims to compare school HR development models between developed and developing countries and to analyze the hindering factors for TQM implementation in developing nations. Using a library research method with a Systematic Literature Review (SLR) approach, this study synthesizes data from reputable journals and international reports. The findings reveal fundamental disparities: developed countries employ school-based professional development models (bottom-up), strict meritocratic recruitment, and instructional leadership. Conversely, developing countries tend to use centralized approaches (top-down), are constrained by politicized recruitment, and are trapped in a culture of administrative compliance. In conclusion, TQM adaptation in developing countries cannot merely imitate technical procedures but must be accompanied by an organizational cultural transformation towards intrinsic professionalism and responsible decentralization.